Pengaruh Regulasi Emosi terhadap Psychological Well-Being pada Mahasiswa Psikologi UNP Angkatan 2021 - Rani Rafika Duri; Kartika Aulia Rahmi; Yuli Rahmadini; Amalia Kartika Yani; Apriyani Apriyani; Maria Weni Gowasa (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
Students are a group of groups in society who have the opportunity to get higher education with the main task of carrying out educational activities, but students often feel difficulties in academic matters, such as piling up coursework, group work that does not go well, exams that are considered difficult, and final assignments that are not completed, thus affecting students' psychological well-being. Therefore, students can regulate emotions to improve psychological well-being. This study was conducted with the aim of measuring the effect of emotion regulation on psychological well-being in students. The subjects used were 165 UNP students majoring in psychology class of 2021. The method used is quantitative with data analysis using simple regression analysis. The results showed a significance level of 0.000 < 0.05, which means that there is an effect of emotion regulation on psychological well-being in UNP psychology students class of 2021.